Association of HLA-Bw46DR9 combination with juvenile myasthenia gravis in Chinese. - Chen, W H (1993)
One hundred and fifty two Chinese patients with myasthenia gravis in Taiwan were investigated for HLA-A, B, C and DR/DQ typing. HLA-Bw46 and DR9 frequencies were significantly increased in patients compared with the control group, and there was a decrease in DR3. Further analysis between different subgroups of patients showed Bw46 and DR9 were more significantly increased in the juvenile group than in the adult group. No single HLA allele was associated with either clinical type or thymic pathology, but there was an excess of BW46DR9 combination in both juvenile and ocular type patients. The Chinese population with myasthenia gravis is characterised by earlier age at onset, more ocular forms and less clinically severe illness than in whites, and these characteristics indicate a special subgroup that correlates with the strong Bw46DR9 association.